Strategi Pemerintah Kota Bogor dalam Meningkatkan dan Mempertahankan Kualitas Laporan Keuangan - Mochamad Ramdani (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2023)
The Reformation Era has led changes in government system in which people demand a good and clean governance indicated by transparency and accountability of state financial reports. Bogor City Government since 2016 until 2021 able to obtain and maintain a WTP opinion assessment from the BPK on the Regional Government Financial Reports which it made from 2006 to 2015 has never received a WTP opinion assessment. The purpose of the reseach to analyze quality of  financial reports of Bogor city, and to formulate a strategy of quality improvement and maintain on financial reports. This research use primary data collected using questionnaires and interviews. Data sources are related to the method of rating scale analysis to measure the quality of LKPD, SWOT analysis in determining strategy alternatives and the use of QSPM in determining priority strategy. The research result shows quality the financial reports on Bogor city falls into a category of fairly good. The prioritized strategy in improving and maintain the quality of LKPD of Bogor city is leadership reinforcement.